Pengaruh E-Service Quality, Promotion, dan Electronic Word of Mouth Terhadap Purchase Intention pada Pengguna Tokopedia di Kota Bandung - Yuliawati, Yupi; Maspupah, Siti (LPPM Universitas Buana Perjuangan Karawang, 2024)
Nowadays with the rapid development of technology and the internet in Indonesia, it has had an impact on business changes. One of the main changes in consumer behavior is the increase in online purchases. An example of e-commerce in Indonesia that has been widely used by the public is Tokopedia. This research was conducted to determine the effect of e-service quality, promotion, and electronic word of mouth on purchase intention. The research was conducted using descriptive and verification methods using a quantitative approach. The sample of this study were 400 respondents. The research was conducted using probability sampling technique, which was collected through distributing questionnaires to 400 respondents as Tokopedia users in Bandung City. The data analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (T Test), simultaneous tests (F Test), and coefficient of determination tests. Data processing using IBM SPSS 21 software. The results showed that the eservice quality variable had a positive and significant effect on purchase intention. Promotion variables have a positive and significant effect on purchase intention. Electronic word of mouth variables have a positive and significant effect on purchase intention. Then the results showed that the variables of e-service quality, promotion,and electronic word of mouth simultaneously had a positive and significant effect on purchase intention.